A study on preparation and properties of carbon materials/myristic acid composite phase change thermal energy storage materials. (3rd July 2019) - He, Meizhi; Yang, Luwei; Zhang, Zhentao; Yang, Junling
ABSTRACT: Microscale graphite (Gr) and nanoscale multi-walled carbon nanotubes (MWCNTs) were chosen to modify the organic phase change material (PCM) of myristic acid (MA). The Gr/MA and MWCNTs/MA composite PCMs were prepared by adding the carbon materials at different mass fractions into MA. The experimental results indicated that both Gr and MWCNTs could enhance the thermal conductivity of MA. For the 3 wt% loading, the solid thermal conductivity of MA increased by 37.42% with Gr and 62.26% with MWCNTs. The FT-IR spectra showed that the reactions between carbon materials and MA were physical. The DSC results illustrated that the phase change latent heats of the composite PCMs decreased gradually with the additives increasing. Gr and MWCNTs strengthened the thermal stability of MA. The heat release rates of the composite PCMs accelerated. Three hundred thermal cycles of the chosen composite PCMs revealed that the prepared composite PCMs presented good thermal cycling stability.